(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
To expand the knowledge on the structure of the microbiota of the nasopharynx of healthy children in different age groups, the authors examined 84 relatively healthy children aged 3 to 12 years old by the method of gas chromatography with mass spectrometry of microbial markers. The examined children were split into 3 groups: 3 to 5 years old (n=28), 6 to 7 (n=27), and 8 to 12 (n=29), respectively. All the patients underwent profound clinical examination: general blood assay, immunologic blood assay, anterior active rhinomanometry, pulse pulseoxymetry, and the study of the microbiota of the nasopharynx with mass spectrometry of microbial markers. It was established that along with a cultivated part of the microbiota, this method allowed the authors to identify microorganisms that are hard to detect and, thus, to expand the knowledge on the normal colonization of the nasopharynx mucosa.